The death penalty: four problems and new philosophical perspectives - Ichinose, M (University of Oxford, Oxford Uehiro Centre for Practical Ethics, 2017)
This paper aims at bringing a new philosophical perspective to the current debate on the death penalty through a discussion of peculiar kinds of uncertainties that surround the death penalty. I focus on laying out the philosophical argument, with the aim of stimulating and restructuring the death penalty debate. I will begin by describing views about punishment that argue in favour of either retaining the death penalty (‘retentionism’) or abolishing it (‘abolitionism’). I will then argue that we should not ignore the so-called “whom-question”, i.e. “To whom should we justify the system of punishment?” I identify three distinct chronological stages to address this problem, namely, “the Harm Stage”, “the Blame Stage”, and “the Danger Stage”. I will also identify four problems arising from specific kinds of uncertainties present in current death penalty debates: (1) uncertainty in harm, (2) uncertainty in blame, (3) uncertainty in rights, and (4) uncertainty in causal consequences. In the course of examining these four problems, I will propose an ‘impossibilist’ position towards the death penalty, according to which the notion of the death penalty is inherently contradictory. Finally, I will suggest that it may be possible to apply this philosophical perspective to the justice system more broadly, in particular to the maximalist approach to restorative justice.